Application of inclined plates in the separation of oil and water - Uthit Thipsuwan; Nguyen Cong Thanh; Samorn Muttamara; Australian Government (Bangkok : Asian Institute of Technology, 1976)
An inclined plate separator was designed for separation of free oil and water from oily waste. The parameters investigated were length of plate, plate spacing and angle of inclination of plate pack. In addition, influence of influent oil content, temperature and pH which affect the separator performance was also studied. The analysis of oil globule size distribution and grade efficiency of effluent was included as well. It was found that the optimum relationship of plate length and plate spacing, l/d, is in the range 20 to 40, and the optimum angle of inclination is at 45 degrees. It was also found that oil separation efficiency was greater with influent of high oil content than one with low oil content. A temperature of 60°c and pH adjustment of 4 or 9 are recommended for demulsion of oily emulsion.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Petroleum pollution of water